Market valuation and deregulation of electric utilities - Blacconiere, Walter G.; Johnson, Marilyn F.; Johnson, Mark S. (Journal of Accounting and Economics, 2000)
This study examines the effect of ongoing deregulation in the electric utility industry on the relation between market value, book value, and earnings. We predict that deregulation decreases (increases) the relative importance of book value (earnings) in explaining price. We test this prediction by examining changes in the value relevance of book value and earnings during the 1988–1996 time period for a sample of large, investor-owned electric utilities. We find that the regression coefficients and incremental explanatory power related to book value (earnings) have decreased (increased) over this time period. These results are generally robust in sensitivity analysis.